IMPROVEMENT OF CLEAN WATER FACILITIES THROUGH THE MAKING OF CLEAN WATER FACILITIES AND WATER TREATMENT MEDIA IN RAWA JAYA VILLAGE, PEMULUTAN DISTRICT, OGAN ILIR REGENCY IN 2021 - Kamidi, Priyadi; Kamsul, Kamsul; Navianti, Diah (LPPM Univ. Ibn Khaldun Bogor, 2022)
Clean water is a very vital need for the community and its role can cause disease if it is not monitored for quality and clean water facilities. The community's clean water facilities need to be monitored for elements that can pollute clean water that needs improvement so that the quality of clean water can be maintained. The coverage of clean water facilities can be increased through the manufacture of clean water facilities and the use of raw water by processing it first so that the physical quality of water meets health requirements. The geographical condition of a residential area in the swamp area and riverbanks becomes a problem and challenge in obtaining clean water sources for the community. Several efforts must be made in anticipating negative impacts, including the creation of clean water facilities and water treatment media in reducing the levels of pollutants in the water. In this community service, the object of service is the Clean Water Facility which is still low at 5.4%, and the use of surface water that has not been treated so that water treatment media is needed to meet health requirements to be used as a source of clean water for the community. Making clean water facilities and water treatment systems will improve the quality of water that will be used by the community.